The Relationship Between Climate Factors and Vector Density with the Incidence of Dengue Hemorrhagic Fever in East Jakarta - Juwita, Disma; Maemun, Siti; Wibowo, Agus Ari; Suprono; Windiyaningsih, Cicilia (The Indonesian Journal of Infectious Diseases, 2025)
Background: Dengue fever is a vector-borne disease. The high incidence of DHF in an area is influenced by living things (vector density) and non-living things (air temperature, climate, humidity, and rainfall). The purpose of the study was to determine the relationship between air temperature, climate, vector density, rainfall, humidity, and the incidence of DHF in East Jakarta in 2022. Methods: This research was an observational ecological study. This research was conducted in Cakung and Pasar Rebo sub-districts, East Jakarta. Secondary data sources were from the VBPP laboratory, BBTKL PP Jakarta, and BMKG Indonesia. Results: The results showed that the container index (CI) correlated with the incidence of DHF (r = 0.118, p = 0.001), as well as the number of ownership-positive containers for larvae correlated with the incidence of DHF (r = 0.113, p = 0.001). Meanwhile, the variables of temperature, humidity, and the free number of larvae did not correlate with the incidence of DHF. Conclusion: It is expected that the community actively drains regularly and closes water storage containers at home.